STRATEGI PEMERINTAH DAERAH DALAM MENERTIBKAN ADMINISTRASI PENDUDUK PINDAH DATANG DI KOTA PALU PROVINSI SULAWESI TENGAH - Eka Putra Kurniyanto, Prastama; Simangunsong, Fernandes (Universitas Islam Majapahit, Indonesia, 2022)
This study aims to determine and analyze the Regional Government Strategy in Ordering the Administration of Moving PopulationsCome, to find out and analyze the supporting and inhibiting factors of the Regional Government Strategy in Ordering Population AdministrationMoving and Coming, as well as to find out and analyze the efforts made in overcoming the inhibiting factors of the Regional Government Strategy inControlling the Administration of Migratory Residents in Palu City, Central Sulawesi Province. This research uses Strategy Theory from Hunger DanWhelen (2003) as an analytical knife where in the theory of Hunger and Whelen Strategy includes 4 (four) indicators namely Environmental Observation,Strategy Formulation, Strategy Implementation, and Evaluation and Control. The research method used is descriptive qualitative methodwith an inductive approach. Data collection techniques were carried out by means of interviews, observation, and documentation. Interviewed informantsnamely the Head of the Population and Civil Registration Service, the Head of the Population Registration Service Division, the Head of the Population Migration Section,Head of Mantikulore sub-district, Tawaeli sub-district head, and the community which includes community leaders and youth leaders. Based on the results of research that hascarried out, in overcoming the problem of relocating residents, the local government through the Department of Population and Civil Registration of the City of Paluimplementing strategies that are already quite good, but public awareness still needs to be improved.